2018
DOI: 10.1007/s00246-018-1964-y
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Risk Analyses for Postcardiotomy Extracorporeal Membrane Oxygenation in Children: A Review of Early and Intermediate Outcomes

Abstract: We evaluated the morbidity and mortality of children requiring postcardiotomy extracorporeal membrane oxygenation (ECMO) to determine independent factors affecting early and intermediate outcomes. Between January 2002 and December 2015, 79 instances of ECMO after cardiac surgery in 73 children were retrospectively reviewed. Follow-up was completed in December 2016. Predictive risk analyses were employed concerning weaning of ECMO, hospital discharge, and mortality after discharge. Age and weight were 14.9 ± 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 37 publications
(56 reference statements)
1
27
0
Order By: Relevance
“…In pediatric cardiac patients, mechanical complications were reported as occurring in 46.9%, hemorrhagic complications in 59.7%, neurological complications in 23.1%, renal complications in 52.5%, cardiac complications in 98.5%, pulmonary complications in 7.8%, and infectious complications in 12.2% of the cases. 15 In our study, mechanical complications were found to occur in 9.8% of the cases. In our previous study, the incidence of mechanical complications was similarly 9% in patients receiving ECMO with the Medos DP3 system.…”
Section: Discussionmentioning
confidence: 45%
See 3 more Smart Citations
“…In pediatric cardiac patients, mechanical complications were reported as occurring in 46.9%, hemorrhagic complications in 59.7%, neurological complications in 23.1%, renal complications in 52.5%, cardiac complications in 98.5%, pulmonary complications in 7.8%, and infectious complications in 12.2% of the cases. 15 In our study, mechanical complications were found to occur in 9.8% of the cases. In our previous study, the incidence of mechanical complications was similarly 9% in patients receiving ECMO with the Medos DP3 system.…”
Section: Discussionmentioning
confidence: 45%
“…There have also been reports showing that the development of hemorrhagic complications has a negative effect on weaning and discharge. 15,37 In our study, we observed statistically significant differences between the survivor-todischarge and non-survivor groups in terms of mechanical (p = 0.02), neurological (p = 0.001), renal (p = 0.001), and infectious (p = 0.01) complications.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…The survival after VA ECMO in children varies between 36 to 48%. [4][5][6][7][8][9][10] The children in our study had a median age and weight of 60 days and 3.4 kg, respectively. Eighty five percent of our study children underwent arterial switch operation (RACHS-4).…”
Section: Discussionmentioning
confidence: 83%